Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Unknown speaker. Under speaker: Alexander Berkman
Funeral of Kropotkin. At the monastery of Novodevičy, where Kropotkin is to be burried. Unknown speaker. Under speaker: Alexander Berkman.